CTNI-04. TRAM-01: A PHASE 2 STUDY OF TRAMETINIB FOR PEDIATRIC PATIENTS WITH NEUROFIBROMATOSIS TYPE 1 AND PLEXIFORM NEUROFIBROMAS. (14th November 2022) - Kiaei, Dorsa Sadat; Larouche, Valerie; Décarie, Jean-Claude; Tabori, Uri; Hawkins, Cynthia; Lippe, Sarah; Ellezam, Benjamin; Ospina, Luis H; Theoret, Yves; Desjardins, Leandra; Metras, Marie-Elaine; Sultan, Serge; et al.
Abstract: BACKGROUND: Plexiform neurofibromas (PN) are observed in up to 50% of patients with neurofibromatosis type 1 (NF1). Trametinib has been used widely to treat PN but limited data has been reported on its efficacy within a clinical trial. METHODS: This ongoing multicenter phase II trial includes patients with pediatric low-grade glioma and PN. Patients received daily oral trametinib (MEK inhibitor) for eighteen 28-day cycles. The volumes of PN were centrally quantified using a new semi-automatic 3D segmentation method. RESULTS: As of May 15, 2022, 46 patients with PN were enrolled in the study and the recruitment was completed for this study arm. Thirty-four completed treatment and were available for analysis. For these patients, the median age was 10.5 years (range 0.7-19.8). The median volume of PN at baseline was 51cm 3 (range 2.6 to 487.6). Among the 34 patients, 28 (82.4%) completed 18 cycles as planned. Two patients discontinued due to adverse reaction, three patients refused to continue treatment and one patient discontinued treatment based on physician decision. Median duration of treatment was 16.8 months (range 2.8 to 16.8). Median duration of follow-up was 30.4 months (range 8.2 to 42). A total of 38 PN were available for volumetric analysis. Using RECIST evaluation, the overall response rate was 13.1%. Volumetric assessment demonstrated an overall response rate of 64.7% (22/34 patients), and 65.8% (25/38 PN) of PN showed a decrease of more than 20% in volume. Median volume change was -30% (range -93.5 to 14.3). Thirty-one patients (91.1%) had durable response without progression (lasting ≥ 1 year). After discontinuation of treatment, one patient underwent surgery and three patients resumed MEK inhibitor. CONCLUSION: We report outcome and volumetric quantification of PN treated with trametinib within a large clinical trial. Based on the current results, trametinib is effective and offers durable response.